Role of trimebutine in conservative therapy of Oddi’s sphincter dysfunction - E. Yu. Plotnikova; T. Yu. Gracheva (Лечащий Врач, 2021)
Oddi’s sphincter dysfunction may have the nature both structural (organic), and functional connected with mobile activity disorders of the sphincter. According to IV Roman Consensus on functional disorders of digestive system 2016, the term «Oddi’s sphincter dysfunction» is recommended for use instead of the terms «postcholecystectomy syndrome», «biliary dyskinesia», etc. The approaches to treatment of Oddi’s sphincter disorders, without its anatomic changes, were considered.